Method to estimate global food waste using an energy gap approach and affluence elasticity - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The approach, along with an internationally comparable consumer food-waste-dataset based on food availability, energy gap and consumer affluence, were published. The authors explain the easiness to use the dataset for constructing a measurable Food Waste Index to assess the current situation regarding progress towards Sustainable Development Goal targets (SDG_12).